The Effects of Using Social Media and Transfer of Knowledge on the Performance of Employees of the Investment Service and One-Stop Integrated Services in Central Bengkulu Regency - Alek Sulaiman Efindi; Ratnawili Ratnawili (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The purpose of this study was to determine the effect of the use of social media and knowledge transfer on the performance of employees of the Investment and One-Stop Services Office in Central Bengkulu Regency. This research uses a quantitative research type method using a quantitative descriptive approach. The population in this study were employees of the Investment and One-Stop Service Office of Central Bengkulu Regency, totaling 40 people by taking samples using total sampling and data collection techniques using observation, interviews and questionnaires. Based on the research results and hypotheses, it shows that social media (X1) is t_hit>t_table (4.643 > 1.664) and (sig α = 0.000 <0.050), and knowledge transfer (X_2) is t_hit>t_table (2.092 > 1.664) and (sig α = 0.040 <0.050), Partially Both Social Media Variables and Knowledge Transfer Have a Significant Influence on Employee Performance. The results of the f test show that Fcount > Ftable, namely (21,589 > 3,965) and (sig α = 0,000 <0.050), simultaneously have a significant effect on employee performance.